A Review on Duplicate and Near Duplicate Documents Detection Technique - Patil Deepali, E; Ghatage Trupti, B; Takmare Sachin, B; Patil Sushama, A (International Journal of Computer Sciences and Engineering, 2025)
Duplicated web pages in consist of identical structure but regarded as clones regarded as clones different data. The identification of similar and near-duplicate pairs in a large collection is a significant the problem with the twide-spread application. The problem deliberated for diverse data types in diverse settings. The contemporary materialization is efficient of the problem identification of the near duplicate Web pages. This is challenging in the web scale to the voluminous data and the high dimensionalities of documents. This review has a fundamental intention to present an up-to-date review of the existing of literature in duplicate and near duplicate detection of general documents and web documents in web crawling. The classification of the existing literature in duplicate and the near duplicate detection techniques and a detailed description of same are the presented so as to make the review more comprehensible.